2019
DOI: 10.1080/19325037.2019.1687364
|View full text |Cite
|
Sign up to set email alerts
|

Worry about Lung Cancer is Related to Numeracy and Risk Perception of Diseases Associated with Smoking

Abstract: Background-Numeracy is one's ability to use numbers in context and influence's decision making and perceptions of health risk. Worry about lung cancer 1 is an indicator of perceived risk 2 and is related to interest in cessation and cancer screening.Purpose-The analysis sought to explore underlying relationships among worry about lung cancer, smoking-related disease risk perceptions, and numeracy in a web-based panel.Methods-A Web-based survey, including a numeracy measure, was completed by 1,682 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The probability that a given treatment will successfully eliminate the tumor, the probability of recurrence, the probability of surviving across a given period, the probability of treatment side effects or debilitating outcomes-these numbers should help to inform decisions among different treatment options. The task of comprehending and comparing these varied statistics is daunting, particularly under stress, and certainly there is evidence that better comprehension of these numbers does influence cancer decisions [55][56][57][58][59][60][61][62][63][64][65] and that decision aids that improve numeric comprehension do support decision processes. [66][67][68] Nevertheless, improving numeric comprehension has limited benefit because comprehension is not the only decision-making hurdle.…”
Section: Discussionmentioning
confidence: 99%
“…The probability that a given treatment will successfully eliminate the tumor, the probability of recurrence, the probability of surviving across a given period, the probability of treatment side effects or debilitating outcomes-these numbers should help to inform decisions among different treatment options. The task of comprehending and comparing these varied statistics is daunting, particularly under stress, and certainly there is evidence that better comprehension of these numbers does influence cancer decisions [55][56][57][58][59][60][61][62][63][64][65] and that decision aids that improve numeric comprehension do support decision processes. [66][67][68] Nevertheless, improving numeric comprehension has limited benefit because comprehension is not the only decision-making hurdle.…”
Section: Discussionmentioning
confidence: 99%
“…There have been researches exploring the relationship between cognitive risk and affective risk. Diaz et al ’.s study showed that perceived risk has a positive association with lung cancer worry (Diaz et al ., 2020). Turner et al reported that individuals’ lung cancer risk perception correlated positively with calculated risk in a screening population (Turner et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Turner et al (Turner et al, 2021) showed that the recruitment for lung cancer screening may be influenced by risk perception. Current studies on risk perception in lung cancer (Park et al, 2009;Greillier et al, 2018;Diaz et al, 2020) have focused on the analysis of influencing factors, such as smoking, in which their study objects have been already involved in screening practices. There is a lack of studies that explore the relevant factors associated with screening participation in populations with high risk of lung cancer and comprehensively analyze their effects.…”
Section: Introductionmentioning
confidence: 99%
“…6 These results are consistent with other studies, as former smokers consistently exhibit less general cancer and lung cancer worry than current smokers. [18][19][20] The HINTS measures did not allow for deeper exploration of the association of perceived information gathering capacity with discussing screening with a provider, but it warrants future consideration. Taken together, the challenge for public health programs and health professionals aiming to increase uptake of lung cancer screening will be to increase the relevance of such screening for former smokers while affirming the health benefits of their long-term cessation.…”
Section: Discussionmentioning
confidence: 99%